Peasant Community of San Mateo Otao - Vasquez Monge, Eduardo (2010)
This article is part of the research we did on the peasant community of San Mateo de Otao, located in the province of Huarochiri. The research included a historical, economic, social and cultural study of this community near metropolitan Lima, as well as its major archaeological sites (Chaupimarca, Marca Marca, Huarichaca) to its value for tourism. Also, identify appropriate appropriate development alternatives to reality and the interests of the community.